2022
DOI: 10.1002/adfm.202209482
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous NASICON‐Type Composite as Low‐Cost, High‐Performance Cathode for Sodium‐Ion Batteries

Abstract: As promising cathode for sodium-ion batteries, Na + Superionic Conductor (NASICON)-type materials have attracted attention owing to their excellent structural stability, superior ionic conductivity, and small volume expansion. However, the vanadium-based NASICON-type cathode with the biotoxicity and exorbitant price of V element and the iron-based cathode with low mean working voltage as well as the intrinsic poor electronic conductivity of polyanionic compounds hinder their practical applications. Herein, a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 48 publications
0
54
0
Order By: Relevance
“…As further modeled by Ceder, Masquelier, et al, the higher voltage plateau of phosphate cathodes is site-limited and strongly depends on the ordering of Na + . Under different Na + ordering and occupation states, the energy barriers for sequential migration of Na + are varied. Given the coordination environment of Na + and the variability of V center in NVP, transition metal cation substitution is therefore considered the most convenient strategy for breaking the symmetry of Na + , thus altering the energy barriers for activating additional Na + . Unfortunately, so far the extraction of such Na + at 4.0 V showed poor reversibility and Na + quickly loses its activity due to the irreversible phase change and structure dilapidation. Therefore, challenges remain not only in the screening of metals with the capability to trigger the accessible additional Na + but also in the ingenious construction of a stable skeleton with moderate energy barriers to allow Na + insertion/extraction in a reversible way. ,− …”
Section: Introductionmentioning
confidence: 99%
“…As further modeled by Ceder, Masquelier, et al, the higher voltage plateau of phosphate cathodes is site-limited and strongly depends on the ordering of Na + . Under different Na + ordering and occupation states, the energy barriers for sequential migration of Na + are varied. Given the coordination environment of Na + and the variability of V center in NVP, transition metal cation substitution is therefore considered the most convenient strategy for breaking the symmetry of Na + , thus altering the energy barriers for activating additional Na + . Unfortunately, so far the extraction of such Na + at 4.0 V showed poor reversibility and Na + quickly loses its activity due to the irreversible phase change and structure dilapidation. Therefore, challenges remain not only in the screening of metals with the capability to trigger the accessible additional Na + but also in the ingenious construction of a stable skeleton with moderate energy barriers to allow Na + insertion/extraction in a reversible way. ,− …”
Section: Introductionmentioning
confidence: 99%
“…The combination of the above advantages will be directly reflected in the high sodium diffusion coefficient of HNVP (Figure 13d) and enable HNVP to release a specific capacity of 77.91 mAh g −1 (area capacity: 3.81 mAh cm −2 ) even at an ultrahigh load of 48.85 mg cm −2 . Guo et al 148 conceived and successfully synthesized a twocarbon layer decoration heterogeneous composite, Na 3 V 2 (PO 4 ) 3 -Na 3 Fe 2 (PO 4 ) (P 2 O 7 ) (NVFPP/C/G) with a two-phase ratio of about 1:1. In the GCD curves, the voltage platforms located at ≈3.45 V, 3.9−4.0 V, and 2.5−3.0 V correspond to the V 4+ /V 3+ redox reactions of NVP, and the V 4+ /V 3+ and Fe 3+ /Fe 2+ redox reactions of NFPP, respectively, which further indicates that NVP and MFPP coexist in NVFPP/C/G base on the insertion and extraction of Na + .…”
Section: Constructing Nvp-based Heterogenous Composite Materialsmentioning
confidence: 99%
“…(i) GCD curve of the first cycle and selected diffraction profiles of the in situ XRD patterns. Reproduced with permission from ref . Copyright 2022 John Wiley and Sons.…”
Section: Constructing Nvp-based Heterogenous Composite Materialsmentioning
confidence: 99%
“…Porosity and the availability of functional groups on carbon surfaces must be altered and regulated by various approaches. [43][44][45][46][47][48][49][50][51][52] The availability of several carbons with diverse types and characteristics as electrodes indicated that the coating of conductive carbon enhanced charge transfer kinetics. 53 Transition metal oxides or hydroxides as electrode materials of supercapacitors allow the formation of the pseudo capacitance property, while they have higher resistance and lower surface area than carbon-based materials and conducting polymers.…”
Section: Introductionmentioning
confidence: 99%